Lithiasis of the main bile duct in laparoscopic surgery - Morelli Brum, Raúl (Cirugía del Uruguay, 1998)
Between March 1991 and october 1995, 277 cholecistectomies were performed by means of laparoscopy by the same author at the same center. Preoperative retrograde endoscopic cholangiography was indicated in five patients with suspicion of lithiasis of the main biliar vía with only one lithiasis confirmation and extraction. Se!ective intraoperative cholangiography was performed in 64 patients (23%); lithiasis of the main biliar vía was found in six patients